Corrosion Damage Behavior of X65/Incoloy 825 Welded Bimetallic Composite Pipe in H2S Environment - Wang, Bingying; Zhang, Tongle; Liu, Yige; Cui, Gan (Frontiers in Materials, 2021)
For the long-term service of X65/Incoloy 825 bimetallic composite pipe girth welds in the H2S environment, the corrosion damage behavior were investigated. Characterizations of welded joint were conducted by OM, SEM, XRD and EDS. And the pitting corrosion’s 3D surface morphology of welded joint in NACE-B solution saturated with H2S was investigated. The results show that composition segregation occurs in the welding process, and the Laves phase appear between dendrites, which leads to the decrease of corrosion resistance. The maximum depth of the corrosion pit is 2.46μm after 30 days, 4.54μm after 60 days, and 10.94μm after 180 days. The cell automata (CA) model of corrosion damage was established based on the MATLAB program, and the basic elements of the CA model were determined. Through the simulation of the electrochemical reaction and diffusion process, the influence of different parameters of the pitting corrosion morphology was determined. The simulation results were compared with experimental data, which is available for the prediction of morphology and size of the corrosion pits on the sample surface after 300 days. The results will be beneficial for long-term service of bimetallic composite pipe.